APPLICATION OF METHODS OF WESTERNMOST POINT AND MULTIPLE REFERENCE POINTS IN DETERMINING ZONE-BASED PRAYER TIME: A STUDY IN SELANGOR - Normana, Mohd Paidi; Man, Saadan; Zainuddin, Mohd Zambri (Online Journal of Research in Islamic Studies, 2014)
The time of a particular prayer (salat) must be accurate for a Muslim to be able to perform the act of worship. This is to avoid the prayer from being performed before its stipulated time. The eccentricity of the Earth’s orbit and the inclination of its axis alter the time of a particular salat every year. The Department of Islamic Development Malaysia (JAKIM) has established the Time Zone Concept for the time of salat with specific terms and conditions based on all zones. Scientifically, two types of techniques are used to specify the time of salat; the Westernmost Point Technique and the Multiple Reference Points Technique. This study was conducted in order to compare each technique based on the calculation between the variant setting points and the effect on the time of salat for the year 2013 in the state of Selangor, Malaysia. This study found that the Multiple Reference Points Technique is more appropriate method in determining the time of salat because it represents the whole entire zone.